CRT Rewind: Teaching toward (the elusive) social justice (Alberta Journal of Educational Research, 2012)
The key event around which this paper is built is the 2010 absolute discharge granted to Eric Tillman, a former (and current) Canadian Football League executive, who pleaded guilty to a sexual assault charge involving a teenage girl in Regina, Saskatchewan, Canada (Pruden, 2010). Drawing on critical race theory as applied to pedagogical spaces (Knaus, 2009; Earick, 2009), it offers a reverse chronology, autoethnographic response to the ruling in the Tillman case, as well as to “public” discourse produced by, and informing, the case itself. Combining autoethnographic reflections and a bricolage of artifacts, it interrogates (im)possibilities of teaching toward social justice with/in pejoratively gendered and racialized social spaces such as those of the Canadian Prairies and offers pedagogical possibilities for speaking to disrupt. L'évènement clé sur lequel se base cet article est l'absolution inconditionnelle accordée à Eric Tillman, un cadre supérieur de la Ligue canadienne de football qui a plaidé coupable à une accusation d'agression sexuelle impliquant une adolescente de Regina, Saskatchewan au Canada (Pruden, 2010). Puisant dans la théorie critique de la race telle qu'elle s'applique aux milieux pédagogiques (Knaus, 2009; Earick, 2009), l'article présente une réaction antichronologique et autoethnographique à la décision dans le cas Tillman et au discours «public» qui en a découlé et qui l'a nourri. Alliant des réflexions autoethnographiques à un mélange d'artéfacts, l'article interroge la possibilité/l'impossibilité d'enseigner vers la justice sociale dans des milieux sociaux où existe la discrimination sexuelle et raciale tels que ceux des Prairies canadiennes. Il présente également des possibilités pédagogiques visant la contestation.